2019
DOI: 10.1159/000504138
|View full text |Cite
|
Sign up to set email alerts
|

True Arterial Stiffness Does Not Change between Dialysis Sessions during 1 Week in Outpatients on Intermitted Hemodialysis

Abstract: Introduction: End-stage renal disease (ESRD) is associated with exponentially elevated cardiovascular mortality. Arterial stiffness (AS) – usually expressed with pulse wave velocity (PWV) – is an established independent predictor of cardiovascular risk beyond the traditional risk factors. Higher PWV values are frequently observed in patients with ESRD. Due to the intrinsic physiologic relationship between PWV and prevailing arterial pressure, PWV can change without relevant changes in the arterial wall structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…We measured PWV prior to HD sessions and there has been debate as to whether HD affects PWV, with some studies observing no effects and others a change in PWV, so questioning whether there is an optimal time make PWV measurements in HD patients 35‐37 . However, more recent studies have shown that after appropriate adjustment for changes in heart rate and blood pressure, 23 then dialysis sessions do not have a significant effect on PWV in the short‐term 38,39 . We chose to use an oscillograph method to determine PWV, as this measures aortic PWV, rather than by applanation tonometry which measures a composite of aortic and one or more conduit arteries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We measured PWV prior to HD sessions and there has been debate as to whether HD affects PWV, with some studies observing no effects and others a change in PWV, so questioning whether there is an optimal time make PWV measurements in HD patients 35‐37 . However, more recent studies have shown that after appropriate adjustment for changes in heart rate and blood pressure, 23 then dialysis sessions do not have a significant effect on PWV in the short‐term 38,39 . We chose to use an oscillograph method to determine PWV, as this measures aortic PWV, rather than by applanation tonometry which measures a composite of aortic and one or more conduit arteries.…”
Section: Discussionmentioning
confidence: 99%
“…[35][36][37] However, more recent studies have shown that after appropriate adjustment for changes in heart rate and blood pressure, 23 then dialysis sessions do not have a significant effect on PWV in the short-term. 38,39 We chose to use an oscillograph method to determine PWV, as this measures aortic PWV, rather than by applanation tonometry which measures a composite of aortic and one or more conduit arteries. As arterial disease and vascular stiffness varies within the arterial tree, we elected to measure aortic PWV, in keeping with the more recent multicenter European trials.…”
Section: Discussionmentioning
confidence: 99%
“…While some earlier reports suggested changes in PWV during HD sessions [16, 17], later studies observed no significant change in PWV during either HD or hemodiafiltration treatments; however, there were changes in augmentation indices as expected associated with the ultrafiltration volumes [18-20]. Although there are many reports of single measurements of PWV in dialysis patients, there are very few studies of 2 or more measurements and no reports of long-term changes.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 (Ref. [ 20 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ]) summarizes the results of several major studies related to serial measurement of arterial stiffness.…”
Section: Serial Measurement Of Arterial Stiffnessmentioning
confidence: 99%